KEANEKARAGAMAN JENIS BURUNG DI KAWASAN MANGROVE GILI SULAT LOMBOK TIMUR - Gito Hadiprayitno; Agil Al Idrus; M. Liwa Ilhamdi; I Gde Mertha (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- Mangrove at Gili Sulat is the important ecosystems that support the lives of  many  wildlife species, one  of  which is species of  birds. Birds use the mangroves  as searching of  food, playing, searching  for  mates,  and  nesting. The aim of  the research is to determine the diversity of  birds species  in  the mangrove area at  Gili Sulat East Lombok. The study was conducted  by observations species of  birds through surveys (direct observation) using binoculars and use the boat (during water conditions  high tide). The result of  this research have found nine species of  birds, consisting  of  four  species  of  water birds (Actitis hypoleucos, Butorides striatus, Chlidonias hibridus, and Egretta Garzetta) and five species  of  birds  terrestrial  (Lalage sueurii, Linkmera lombokia, Nectarinia jugularis, Merops ornatus, and  Zosterops  palpebrosus) .Keywords:  Birds,  Mangroves,  Gili Sulat, East Lombok